PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PREZI PADA PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Eliza Saroha; Naeklan Simbolon (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This study aims to: (1) determine the feasibility of prezi-based learning media, (2) determine the effectiveness of the use of prezi-based learning media in class III SD 101769 Tembung. This type of research is development research using the 4-D Thiagarajan model. In the aspect of media feasibility, the assessment is carried out by material experts, media experts and instructional design experts. In the aspect of the effectiveness of the use of media, learning outcomes tests are conducted by students. The trial subjects consisted of 6 students for limited trials, and 26 students for field trials. Based on the results of the assessment by the three expert validations, an overall average of 87.10% was included in the excellent category. Based on the results of product trials obtained an increase in student learning outcomes compared with the results of the pretest that is equal to 50% in limited trials and 69.23% in broad trials. Thus, it can be concluded that the prezi-based learning media developed are feasible and effective to use.Keywords: Development, Media, Thematic Learning, Prezi